Pattern and clinical profile of children and adolescent visiting psychiatry outpatient department of tertiary health center amid COVID-19 pandemic: A cross-sectional study - Poornima Khadanga; Sarika Dakshikar; Gomati Nadadgalli; Gaurav Eknath Pawar; Madhavi Rairikar (Telangana Journal of Psychiatry, 2026)
ABSTRACT Background: The COVID-19 pandemic with its unparalleled mental health repercussions has impacted people globally and has catalyzed a mental health pandemic among the youth. The detrimental effects on mental health need to be pondered at the earliest. Aims: The aim of the study was to study the behavioral problems among children and adolescents visiting the psychiatry outpatient department (OPD) tertiary health care during the COVID-19 pandemic and its correlation with sociodemographic and clinical variables. Methods: A cross-sectional study was conducted by interviewing 120 participants between 4 and 17 years of age and their parents, visiting psychiatry OPD. Behavioral problems were assessed using the Strength and Difficulties Questionnaire and diagnosed by the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. Statistical analysis was done by SPSS version 21. Results: Attention deficit hyperkinetic disorder (18.3%) was the most frequently presented clinical diagnosis. The total difficulty scale was abnormal in most of the participants with peer problem score contributing the most proportion (63.3%). Increase in screen time showed a positive correlation with conduct problems ( r = 0.22. P = 0.02) and hyperactivity ( r = 0.22, P = 0.02). Conclusion: The study brings to light the pattern of behavioral problems that emerged during recent times of uncertainties among the young ones including those with special needs. The increase in disruptive behaviors with increased screen time needs to be addressed at the earliest.